SIMULTANEOUS DETERMINATION OF CADMIUM, COPPER AND LEAD IN SEA WATER BY ADSORPTIVE STRIPPING VOLTAMMETRY IN THE PRESENCE OF CALCON AS A COMPLEXING AGENT - Deswati Deswati; Hamzar Suyani; Safni Safni; Umiati Loekman; Hilfi Pardi (Universitas Gadjah Mada, 2013)
A selective and sensitive adsorptive stripping voltammetric (AdSV) procedure for the simultaneous determination of cadmium, copper and lead in the sea water was conducted. The aim of this research is to get optimum condition for simultaneous determination of cadmium, copper and lead. Adsorptive stripping voltammetry has been used for determination of trace amount of Cd(II), Cu(II) and Pb (II) by using calcon as a complexing agent. The parameters studied were variation of calcon concentration, pH, accumulation potential and accumulation time. In this study, the optimum conditions were calcon concentration of 0.6 mM, pH = 4.0, accumulation potential of -0.7 V and accumulation time of 80 sec. At the optimum conditions, the relative standard deviation were 8.78%, 3.12%, and 4.02% for Cd(II), Cu(II) and Pb(II) respectively for eight replicates (n = 8) measurements of 10 μg/L mixed standard solution of Cd(II), Cu(II) and Pb(II). The method was applied to the direct simultaneous determination of Cd(II), Cu(II) and Pb(II) in sea water around Bungus, Padang City. Concentration of Cd(II), Cu(II) and Pb(II) in samples were equal to 1.8 μg/L for Cd(II), 38.6 μg/L for Cu(II) and 0.7 μg/L for Pb(II) with recovery of 87.03%, 98.80%, and 95.73%, respectively.